Maternal Group B Streptococcus Prophylaxis Improvement using an Electronic Medical Record Dynamic Order Set - Tomlinson, Mark W.; Baker, Rachael; Ulrich, Jennifer; Shah, Maulin; Marginean, Horia; Girolami, Stephen (American Journal of Perinatology, 2023)
Objective To develop and implement a Group B Streptococcal (GBS) dynamic order set to improve adherence to the American College of Obstetricians and Gynecologists/Centers for Disease Control and Prevention (ACOG/CDC) guidelines.Study Design A team of information technology and clinical experts developed a dynamic order block. The content was patterned after the CDC “Prevent GBS” mobile app. It was then embedded in the labor and delivery/induction order set and piloted at a single high-volume obstetric unit. Following the pilot and incorporation of the 2019 ACOG update of the CDC guidelines, the order set was rolled out in five additional hospitals within a region of a large health system. Information on GBS prophylaxis performance before and after implementation was available for the pilot site and four of the additional hospitals. Information before implementation was obtained electronically from electronic medical record (EMR) laboratory and pharmacy data and supplemented by manual chart review. Postimplementation data were obtained from discrete order set EMR data elements. Adherence to the guidelines before and after were compared using chi-squared test.Results There were 7,114 deliveries before implementation and 4,502 after implementation. Preterm delivery occurred in 6.8 and 6.9%, respectively. There was an increase in appropriate treatment of preterm patients (positive and unknown GBS) delivering after implementation (88.7–99.1%, p < 0.001). More patients were reported to have a penicillin allergy before implementation than after implementation (14.7 vs. 11.1%, respectively, p = 0.01). Associated changes in therapy noted after implementation included a nonsignificant decrease in the proportion reporting a high-risk allergy (50.3 vs. 41.9%, p = 0.18), an increase in the appropriate use of clindamycin and vancomycin (64.4 vs. 92.3%, p < 0.001) and a decrease in clindamycin use in those without sensitivity testing.Conclusion Routine universal use of a dynamic admission labor/induction order set was associated with high and improved adherence to GBS prophylaxis guidelines.Key Points
Keywords: clinical decision support; early-onset GBS disease; EMR decision aid; EMR decision aid; GBS antibiotic prophylaxis; GBS prophylaxis in penicillin allergy